2011
DOI: 10.3928/01477447-20110627-17
|View full text |Cite
|
Sign up to set email alerts
|

Arthrodiatasis for Management of Knee Osteoarthritis

Abstract: Osteoarthritic disease is the result of mechanical and biological events that destabilize the normal processes of degradation and synthesis of articular cartilage chondrocytes, extracellular matrix, and subchondral bone. Osteoarthritis of the knee can cause symptoms ranging from mild to disabling. Initial management of most patients should be nonoperative, but because of the progressive nature of the disease, many patients with osteoarthritis of the knee eventually benefit from operative treatment. Various pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Two studies were excluded as they reported the results of arthroscopic microfracture in combination with KJD and it was the authors opinion that, as microfracture is already an established treatment for cartilaginous loss, it would not be possible to delineate any treatment effect seen. 16,17 The first of these studies by Deie et al reported the outcomes of six knees managed with KJD and microfracture and found at a mean 3-year follow-up significant improvements in Japanese Orthopaedic Association Score, VAS pain score, and radiographic joint space width. 16 The second, by Aly et al, reported the outcomes of 61 knees, 19 managed with KJD, joint debridement and microfracture and 42 managed with joint debridement and microfracture and found that at a mean follow-up of 3 to 5 years the group managed with KJD, joint debridement, and microfracture had significantly improved pain, walking capacity, stair climbing, and radio-graphic joint space width compared with baseline, whereas those treated with joint debridement and microfracture without KJD did not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were excluded as they reported the results of arthroscopic microfracture in combination with KJD and it was the authors opinion that, as microfracture is already an established treatment for cartilaginous loss, it would not be possible to delineate any treatment effect seen. 16,17 The first of these studies by Deie et al reported the outcomes of six knees managed with KJD and microfracture and found at a mean 3-year follow-up significant improvements in Japanese Orthopaedic Association Score, VAS pain score, and radiographic joint space width. 16 The second, by Aly et al, reported the outcomes of 61 knees, 19 managed with KJD, joint debridement and microfracture and 42 managed with joint debridement and microfracture and found that at a mean follow-up of 3 to 5 years the group managed with KJD, joint debridement, and microfracture had significantly improved pain, walking capacity, stair climbing, and radio-graphic joint space width compared with baseline, whereas those treated with joint debridement and microfracture without KJD did not.…”
Section: Resultsmentioning
confidence: 99%
“…16 The second, by Aly et al, reported the outcomes of 61 knees, 19 managed with KJD, joint debridement and microfracture and 42 managed with joint debridement and microfracture and found that at a mean follow-up of 3 to 5 years the group managed with KJD, joint debridement, and microfracture had significantly improved pain, walking capacity, stair climbing, and radio-graphic joint space width compared with baseline, whereas those treated with joint debridement and microfracture without KJD did not. 17 Outcomes of KJD Improvement from Baseline to One Year Post Intervention…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Studies have demonstrated a progressive decrease in pain, normalization of function, and a sustained increase in cartilage thickness as seen on weightbearing radiographs. [14][15][16][17] Arthroscopy [14][15][16] and magnetic resonance imaging (MRI) 14,18 evaluation showed cartilage repair after KJD. As a surrogate marker for cartilage quality, biochemical markers for collagen type-II turnover demonstrated an increase of synthesis over release.…”
Section: Introductionmentioning
confidence: 99%
“…A few treatment options that preserve the joint are available for severe end‐stage knee OA. Knee joint distraction is considered a novel, still experimental, treatment option that has shown long‐term (at least 5 years [Wiegant K, et al: unpublished observations]) clinical benefit, accompanied by tissue structure repair, as evaluated by imaging techniques (radiography and magnetic resonance imaging [MRI]) and analysis of biochemical (collagen turnover) markers ().…”
mentioning
confidence: 99%